The effect of GdYVO4:Eu3+ nanocrystals on the intercellular adhesion of mesenchymal stem cells in vitro - Y. H. Kot; K. V. Kot; N. S. Kavok; V. K. Klochkov (Regulatory Mechanisms in Biosystems, 2023)
Adult stem cells, such as MSCs, spontaneously differentiate in vitro. This makes it difficult both to study this important cell type and to grow large numbers of MSCs for clinical use. While conventional cell cultivation methods cannot cope with this problem, nanostructured materials science offers hope. The effect of small-sized spherical nanoparticles based on orthovanadates of rare-earth elements activated by europium (GdYVO4:Eu3+ nanoparticles, diameter 1–2 nm) on cell-cell adhesion of rat bone marrow mesenchymal stem cells (rBM-MSCs) in vitro was studied using electrophoretic separation of proteins, immunofluorescence and confocal laser scanning microscopy. Our study revealed that rBM-MSCs treated with small-sized GdYVO4:Eu3+ nanoparticles had a significant impairment of intercellular adhesion in vitro. The pre-incubation of mesenchymal stem cells of rat bone marrow with GdYVO4:Eu3+ nanocrystals at a non-toxic concentration of 0.5 µg/mL during 1 hour of cultivation did not lead to significant changes in cell monolayer, the number of cells and the area of cell bodies did not change. However, the density of the monolayer and the area of the cell field decreased after the incubation. The incubation of cells with nanoparticles led to an increase in the area of the intercellular gate – a location of disruption of cell adhesion, compared to cells without nanoparticles in culture medium. The pre-incubation of rBM-MSCs with nanocrystals caused no changes in the content of total cadherins in the plasma membrane; a decrease in the content of cytoplasmic calreticulin and an increase in the content of surface calreticulin; a decrease in the content of free calcium in the cytoplasm, and an increase in protein-bound intercellular calcium and calcium in the extracellular space. The colocalization analysis revealed that the colocalization of calreticulins with cadherins on the outer surface of the plasma membrane of cells significantly increased after the incubation with GdYVO4:Eu3+ nanocrystals. The paper proposes a possible mechanism of reducing the degree of adhesion by nanocrystals. This study emphasizes the possibility of modulating MSCs adhesion using GdYVO4:Eu3+ nanoparticles. The development of new technologies capable of mitigating adhesion is crucial for the development of regenerative strategies using stem cells.